Influence of an unaccustomed increase in training volume vs intensity on performance, hematological and blood-chemical parameters in distance runners - Lehmann, M.; Wieland, H.; Gastmann, U. (The Journal of Sports Medicine and Physical Fitness, 1997)
Experienced distance runners (N = 8) were subjected to an unaccustomed 103% increase in training volume over four weeks. One year later 9 runners were subjected to a 152% increase in training intensity for activities. Seven athletes participated in both studies. Volume increased training produced performance improvements after two weeks but that stopped between weeks 3 and 4. Maximum performance worsened at the end of the period indicating the onset of overtraining. During increased intensity training, submaximum and maximum performances increased continuously. When compared to increased intensity values, increased volume training caused significant reductions in white blood cell count, serum iron, ferritin, VLDL-cholesterol, LDL-cholesterol, albumin, resting and maximum FFA, maximum lactate, glucose (resting, submaximal, maximal), summed amino acid, and ammonia concentrations at all levels. However, there was no single blood facet that could be used to indicate overtraining in all Ss. Only when performance and particular blood reactions are taken togetherfor individuals can overtraining be better diagnosed. Implication: Blood changes do occur with overtraining but no one indicator is useful as a universal diagnostic factor. Normally, a group of "unusual" levels in some blood factors along with diminished performance is adequate to diagnose an overtrained state. Overtraining, can be avoided by interpreting overreaching as a first stage breakdown rather than questioning whether reduced performances in overreaching are caused by a lack of effort, intestinal fortitude, or inadequate "mental toughness."